Method for preparing battery-grade lithium carbonate by acid leaching of lithium sulfate solution
By using a combination technology of calcium hydroxide and modified adsorbent microspheres in the acid-immersed lithium sulfate solution, the problems of difficulty and high cost of lithium recycling are solved, and effective recycling of high-purity lithium carbonate and low-cost production are achieved.
Patent Information
- Application Number
- CN202411301433.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-18
- Publication Date
- 2024-12-20
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
In the prior art, the recovery of lithium in the acid-immersed lithium sulfate solution is difficult and has high recycling cost. The selective adsorption ability and regeneration and recycling performance of traditional adsorbents need to be improved.
Pretreatment by adding calcium hydroxide solution to the acid leach extract, adjusting the pH value, and adsorption and desorption of lithium are performed using modified adsorbent microspheres, and then high-purity lithium carbonate is obtained through sodium carbonate precipitation and purification processes.
It improves the recovery rate and purity of lithium, reduces production costs, simplifies the regeneration process, and enhances the selectivity and recycling performance of adsorbents.
Smart Images

Figure BDA0005047778510000041 
Figure BDA0005047778510000081 
Figure BDA0005047778510000224
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of lithium recovery and regeneration, and in particular to a method for preparing battery-grade lithium carbonate by acid leaching of lithium sulfate solution. Background Art
[0002] As the new energy vehicle industry enters its golden period of development, the power lithium battery industry has seen explosive growth, and the demand for lithium carbonate has also increased year by year. As strategic resources in the 21st century, metallic lithium and lithium salts are widely used in the battery industry, glass and ceramics industry, lubricants, refrigerants, nuclear industry, optoelectronics industry and other fields. The use of lithium-containing fluoride salts results in the generation of a large amount of lithium-containing electrolytic aluminum waste slag. If it is reasonably recycled and utilized, it will help alleviate the lithium pressure brought by the new energy industry.
[0003] In aluminum electrolysis production, in order to improve the properties of the electrolyte and achieve the purpose of improving current efficiency and reducing energy consumption, in addition to adding aluminum fluoride or cryolite to the electrolyte, lithium fluoride is also added to the electrolyte to reduce the initial crystallization temperature of the electrolyte and reduce fluorine emissions, which promotes energy conservation and consumption reduction in electrolytic aluminum enterprises. The electrolyte system with a high lithium salt content results in low electrolytic production cell temperature, poor alumina solubility, and a lot of precipitation at the bottom of the electrolytic cell. The lithium-containing solid waste produced by electrolytic aluminum contains about 1.37% lithium, and the remaining main components are sodium, fluorine, aluminum, calcium, iron, etc. Sulfuric acid is usually used as the leaching solution for acid leaching to prepare an acid-leached lithium sulfate solution containing other impurities.
[0004] In the prior art, the lithium in the acid-leached lithium sulfate solution is regenerated and recovered by an alkali precipitation method. After the impurities in the acid-leached lithium sulfate solution are initially precipitated, most of the solvent water is removed by vacuum concentration, and then the crude lithium carbonate is purified after precipitation with sodium carbonate. However, the boiling point of water is relatively high, and vacuum concentration requires a lot of energy and time. The regeneration of lithium carbonate is difficult. Moreover, after the solvent is concentrated, a large amount of impurities are re-enriched, and multiple purifications are required to obtain battery-grade lithium carbonate. The recovery of lithium in the acid-leached lithium sulfate is difficult and the recovery cost is high.
[0005] Selectively adsorbing lithium in the solution with an adsorbent and then desorbing it can effectively avoid the problems of high energy consumption and impurity enrichment caused by reduced pressure concentration. However, the selective adsorption capacity of traditional adsorbents for lithium in the solution needs to be further improved, resulting in the inability to completely adsorb lithium in the solution. The lithium recovery rate is only around 60%, and a large amount of impurities are adsorbed on the adsorbent, resulting in the lithium purity being difficult to meet the requirements of battery-grade lithium carbonate. In addition, after the traditional adsorbent is recycled, its selective adsorption capacity for lithium decreases rapidly, and the regeneration and recycling performance of the adsorbent needs to be further improved.
[0006] In view of the technical defects in this aspect, a solution is now proposed. Summary of the invention
[0007] The object of the present invention is to provide a method for preparing battery-grade lithium carbonate by acid leaching lithium sulfate solution, which is used to solve the technical problems in the prior art that the recovery of lithium in the acid leached lithium sulfate is difficult and the recovery cost is high, and the selective adsorption capacity of traditional adsorbents for lithium in the solution and the regeneration and recycling performance need to be further improved.
[0008] The purpose of the present invention can be achieved by the following technical scheme: A method for preparing battery-grade lithium carbonate by acid leaching lithium sulfate solution, comprising the following steps:
[0009] S1. Add the acid leaching extract to the reactor and stir. Lower the temperature of the reactor to 15-25°C, add calcium hydroxide solution to the reactor, adjust the pH of the system to 9-10, raise the temperature of the reactor to room temperature, stir for 20-30 minutes, and post-treat to obtain a pre-treated solution;
[0010] S2, adding the pretreatment solution and the adsorbent microspheres into a reaction kettle and stirring, stirring for 50-60 minutes at room temperature, and post-treating to obtain adsorption-saturated adsorbent microspheres;
[0011] S3, desorbing the adsorbent microspheres to obtain a lithium-containing purified liquid;
[0012] S4, adding saturated sodium carbonate solution to the lithium-containing purified liquid, adjusting the system pH to 8-9, and post-treating to obtain crude lithium carbonate;
[0013] S5. Purify the crude lithium carbonate to obtain lithium carbonate.
[0014] Furthermore, in step S1, the post-treatment includes: after the reaction is completed, filtering, washing the filter cake twice with a 3wt% sodium hydroxide solution and then drying, collecting the filtrate to obtain a pretreatment solution; in step S2, the dosage ratio of the pretreatment solution to the adsorbent microspheres is 50mL:2-3g, and the post-treatment includes: after the adsorption is completed, filtering, washing the filter cake twice with a sodium hydroxide solution with a pH of 9-10 and then drying, to obtain adsorption-saturated adsorbent microspheres.
[0015] Further, in step S3, desorption includes: adding the adsorbent microspheres saturated with adsorption and 0.5 mol / L hydrochloric acid solution in a dosage ratio of 1 g: 5 mL into a reactor and stirring, raising the temperature of the reactor to 40-50° C., keeping warm for 30-50 min, filtering, washing the filter cake twice with 0.5 mol / L hydrochloric acid solution and then drying, collecting the filtrate, and obtaining a lithium-containing purified liquid.
[0016] Furthermore, in step S4, post-treatment includes: after the reaction is completed, filtering, washing the filter cake with 3-8°C purified water for 3 times and then drying, transferring the filter cake to a drying oven at a temperature of 70-80°C, and vacuum drying to constant weight to obtain crude lithium carbonate.
[0017] Furthermore, in step S5, the purification process includes: adding the crude lithium carbonate and deionized water in a ratio of 1g:10mL to a reactor, raising the temperature of the reactor to 85-95°C, stirring until the system is dissolved, filtering while hot into a crystallization kettle and stirring, lowering the temperature of the crystallization kettle to 15-18°C, a large amount of solid precipitates, suction filtering, washing the filter cake with 50vol% anhydrous ethanol aqueous solution 3 times and then draining, drying the filter cake at 70-80°C and transferring it to a tubular furnace at a temperature of 250-260°C, and drying to constant weight to obtain lithium carbonate.
[0018] Further, the adsorbent microspheres are processed by the following steps:
[0019] A1, polysulfone and dichloromethane are added to a nitrogen-protected reactor, stirred at room temperature until the polysulfone is dissolved, the reactor temperature is lowered to 6-8°C, trioxymethylene is added to the reactor, stirred for 20-30 minutes, trimethylsilyl chloride is added dropwise to the reactor, and then a catalyst is added to the reactor, stirred for 25-35 minutes, the reactor temperature is raised to reflux, the reaction is kept warm for 12-16 hours, and post-processed to obtain modified polysulfone;
[0020] The synthetic reaction formula of modified polysulfone is:
[0021]
[0022] The synthetic reaction mechanism of modified polysulfone is:
[0023] After polysulfone is dissolved in dichloromethane as a solvent, under the action of a catalyst, trioxymethylene is catalyzed to decompose into formaldehyde, trimethylchlorosilane reacts with formaldehyde to generate chloromethylsilane intermediates, and these intermediates subsequently react with polysulfone to introduce chloromethyl groups into the polysulfone molecules. After the reaction is completed, a large amount of ethanol is added to quench the reaction, and the addition of ethanol destroys the solvation effect in the reaction system, so that the modified polysulfone is precipitated from the solution, and the modified polysulfone is prepared.
[0024] A2, adding modified polysulfone, polyethylene glycol and N,N-dimethylformamide into a reactor, raising the temperature of the reactor to 65-75°C, stirring until the system is dissolved, adding modified adsorption filler into the reactor, stirring for 20-30 minutes, vacuum degassing, and obtaining a mixed solution;
[0025] A3, the mixed solution was added dropwise into a reactor equipped with a coagulation bath, aged at room temperature for 40-60 min, the reactor was stirred, sodium hydroxide solution was added dropwise into the reactor, the pH of the system was adjusted to 9-10, stirred for 3-5 h, and post-processed to obtain a crude adsorbent;
[0026] A4. Add the crude adsorbent and anhydrous ethanol into a reactor and stir. Raise the temperature of the reactor to 60-70°C and stir for 40-60 minutes. Post-treat to obtain adsorbent microspheres.
[0027] The synthetic reaction mechanism of adsorbent microspheres is:
[0028] The mixed liquid consisting of modified polysulfone, polyethylene glycol and modified adsorbent filler, after entering into a coagulation bath, forms a microspherical structure in the coagulation bath with modified polysulfone as a curing agent, and the modified polysulfone and the modified halogen on the modified adsorbent react with the amino group on the modified chitosan molecule to embed the modified chitosan on the outside of the microsphere, and under alkaline conditions, the chitosan precipitates and solidifies from the solution to prepare a crude adsorbent; the crude adsorbent is washed with anhydrous ethanol to remove soluble impurities such as N,N-dimethylformamide or polyethylene glycol in the crude adsorbent to obtain adsorbent microspheres with a porous structure.
[0029] Furthermore, in step A1, the amount ratio of the polysulfone, dichloromethane, trioxymethylene, trimethylsilyl chloride and catalyst is 10g:300mL:9g:30mL:0.5g, the catalyst is anhydrous tin tetrachloride, and the post-treatment includes: after the reaction is completed, the temperature of the reactor is lowered to room temperature, ethanol is slowly added to the reactor, stirred and dispersed for 20-30min, filtered, the filter cake is washed twice with anhydrous ethanol and then dried, the filter cake is transferred to a drying oven at a temperature of 50-60°C, and vacuum dried to constant weight to obtain modified polysulfone.
[0030] Furthermore, in step A2, the amount ratio of the modified polysulfone, polyethylene glycol, N,N-dimethylformamide and modified adsorption filler is 8-10g:10-12g:60mL:20-25g; in step A3, the volume ratio of the mixed solution to the coagulation bath is 1:3, the sodium hydroxide solution is composed of 2mol / L sodium hydroxide solution and sodium dodecyl sulfate in a weight ratio of 10:1, and the post-treatment includes: after the reaction is completed, filtering, washing the filter cake with purified water until neutral and then drying, transferring the filter cake to a drying oven at a temperature of 70-80°C, and vacuum drying to constant weight to obtain a crude adsorbent.
[0031] Furthermore, in step A4, the ratio of the crude adsorbent to anhydrous ethanol is 1 g:20 mL, and the post-treatment includes: after the reaction is completed, the temperature of the reactor is lowered to room temperature, filtered, the filter cake is washed with purified water three times and then dried, the filter cake is transferred to a drying oven at a temperature of 70-80°C, and vacuum dried to constant weight to obtain adsorbent microspheres.
[0032] Further, the modified adsorption filler in step A is obtained by processing the following steps:
[0033] B1. Place the multi-metal mixture in a tube furnace, increase the temperature of the tube furnace to 800-900°C at a heating rate of 3-5°C / min, keep the mixture warm for 4-6 hours, cool it down and discharge it to obtain a filler precursor;
[0034] B2. After continuously eluting the filler precursor with 0.5 mol / L hydrochloric acid for 40-60 min, use purified water to elute for 10-15 min, transfer the eluted particles to a drying oven at a temperature of 75-85°C, and dry to constant weight to obtain an adsorption filler;
[0035] B3. Add the adsorption filler, 3-chloropropyltrimethoxysilane and anhydrous ethanol into the reactor and stir. The temperature of the reactor is raised to 50-60° C., and alkali solution is added into the reactor. The reaction mixture is stirred for 30-50 min at the temperature. The modified adsorption filler is obtained by post-treatment.
[0036] The synthetic reaction mechanism of the modified adsorption filler is:
[0037] Under a high temperature roasting environment of 800-900°C, manganese carbonate and lithium carbonate decompose to form metal oxides, while titanium and silicon oxides undergo phase change or crystallization, promoting the interaction between the metal oxides to form a more stable composite oxide structure, thereby preparing a filler precursor; the filler precursor is continuously eluted with hydrochloric acid to remove excess metal oxides and impurities in the filler, thereby forming adsorption pores and channels to obtain an adsorption filler; under alkaline conditions, 3-chloropropyltrimethoxysilane is hydrolyzed and reacts with hydroxyl groups on the surface of the adsorption filler to form a chemical bond, thereby forming a 3-chloropropyltrimethoxysilane modification on the outside of the adsorption filler to prepare a modified adsorption filler.
[0038] Furthermore, in step B3, the amount ratio of the adsorption filler, 3-chloropropyltrimethoxysilane, anhydrous ethanol and alkali solution is 5g:2g:30mL:8mL, the alkali solution is 0.5mol / L sodium hydroxide solution, and the post-treatment includes: after the reaction is completed, the temperature of the reactor is lowered to room temperature, filtered, the filter cake is washed with purified water 3 times and then dried, the filter cake is transferred to a drying oven at a temperature of 75-85°C, and dried to constant weight to obtain a modified adsorption filler.
[0039] Further, the multi-metal mixture is processed by the following steps:
[0040] C1. Add manganese carbonate and lithium carbonate into a ball mill, ball mill for 40-60 minutes, and pass through a 100-mesh sieve to obtain a mixed powder;
[0041] C2. Add the mixed powder, tetrabutyl titanate, ethyl orthosilicate, anhydrous ethanol and purified water into a reactor and stir. The temperature of the reactor is raised to 50-60° C. and stirred for 3-5 hours. Post-process to obtain a multi-metal mixture.
[0042] The synthesis reaction mechanism of multi-metal mixture is:
[0043] The size of metal carbonate particles is reduced by ball-milling manganese carbonate and lithium carbonate, and tetrabutyl titanate and ethyl orthosilicate are hydrolyzed in an ethanol aqueous solution to form colloidal particles of titanium and silicon hydroxides. At the same time, manganese carbonate and lithium carbonate are partially dissolved and interact with the colloidal particles. As the reaction proceeds, the colloidal particles gradually aggregate and cross-link to form a gel with a three-dimensional network structure. The solvent in the gel material is removed by negative pressure and high temperature, so that the gel is further solidified and converted into a porous solid to obtain a multi-metal mixture.
[0044] Furthermore, in step C1, the weight ratio of manganese carbonate to lithium carbonate is 1:2; in step C2, the amount ratio of the mixed powder, tetrabutyl titanate, ethyl orthosilicate, anhydrous ethanol and purified water is 3g:1g:2g:20mL:2g, and the post-treatment includes: after the reaction is completed, the temperature of the reactor is increased to 70-80°C, the solvent is evaporated under reduced pressure to obtain a solid, the solid is placed in a drying oven at a temperature of 80-90°C, air dried for 6-8h, crushed, and passed through an 80-mesh sieve to obtain a multi-metal mixture.
[0045] Further, the coagulation bath is processed by the following steps:
[0046] D1. Add 2-hydroxymethyl-12-crown-4, sodium hydride and N,N-dimethylformamide to a nitrogen-protected reactor and stir. Raise the temperature of the reactor to 55-65°C, keep warm and stir until the system turns light brown. Add epichlorohydrin to the reactor and stir for 70-80h. Add chitosan solution to the reactor and keep warm for 20-30h. Post-treat to obtain modified chitosan.
[0047] The synthetic reaction formula of modified chitosan is:
[0048]
[0049] In the formula
[0050] The synthetic reaction mechanism of modified chitosan is:
[0051] Sodium hydride, as a strong base, can dissociate hydroxide ions in N,N-dimethylformamide. Epichlorohydrin is easy to open the ring under alkaline conditions to undergo substitution reaction with the hydroxymethyl group on 2-hydroxymethyl-12-crown-4, forming chloro substitution on the crown ether. In the chitosan solution, sodium hydride reacts with acetic acid, and excess acetic acid causes the reaction system to change from alkaline to acidic. Under acidic conditions, the C-Cl bond breaks and undergoes chloro substitution reaction with the amino group on the chitosan molecule to prepare modified chitosan.
[0052] D2. Add the modified chitosan and the dissolving solution into the reactor and stir until the system is dissolved to obtain a coagulation bath.
[0053] Furthermore, in step D1, the amount ratio of the 2-hydroxymethyl-12-crown-4, sodium hydride, N,N-dimethylformamide, epichlorohydrin and chitosan solution is 2g:0.1g:10mL:0.9g:30mL, the chitosan solution is composed of chitosan and 2wt% acetic acid solution in an amount ratio of 1g:10mL, and the post-treatment includes: after the reaction is completed, the temperature of the reactor is increased to 85-95°C, the solvent is evaporated under reduced pressure to obtain a solid, the solid is washed with purified water 3 times and then dried, the filter cake is transferred to a drying oven at a temperature of 70-80°C, and vacuum dried to constant weight to obtain modified chitosan; in step D2, the amount ratio of the modified chitosan and the dissolving solution is 1g:7mL, and the dissolving solution is composed of 2wt% acetic acid solution and ethanol in a volume ratio of 4:6.
[0054] The present invention has the following beneficial effects:
[0055] 1. The present invention provides a method for preparing battery-grade lithium carbonate by acid leaching lithium sulfate solution. The acid leaching extract is treated with a calcium hydroxide solution to promote the precipitation of iron, silicon, phosphate and sulfate ions in the acid leaching extract in the calcium hydroxide system, change the existence form of lithium ions in the acid leaching extract, separate lithium ions from impurity ions in the acid leaching extract, preliminarily purify the acid leaching extract, adsorb lithium in the pretreatment solution under alkaline conditions by an adsorbent, reduce the distillation and concentration steps, and reduce production costs. Under alkaline conditions, lithium ions in the pretreatment solution are more easily adsorbed by adsorbent microspheres, thereby improving the extraction and regeneration efficiency of lithium ions in the pretreatment solution. After precipitation with sodium carbonate, the purification process of crude lithium carbonate is optimized to prepare a high-purity lithium carbonate material. When lithium in the acid leaching extract is recovered, the lithium regeneration process is optimized, which not only effectively reduces production energy consumption and simplifies the regeneration process, but also improves the recovery rate and purity of lithium carbonate.
[0056] 2. The present invention provides an acid-leached lithium sulfate solution for preparing battery-grade lithium carbonate adsorbent microspheres, wherein a mixed powder consisting of manganese carbonate and lithium carbonate is mixed with tetrabutyl titanate and ethyl orthosilicate to prepare a mixture of lithium, manganese, titanium multi-metal and silicon. During high-temperature roasting, manganese carbonate and lithium carbonate will decompose to generate corresponding metal oxides (such as manganese dioxide and lithium oxide). These metal oxides not only provide more active sites for adsorption fillers, but also form more complex composite oxide structures through interaction with titanium metal oxides, and remove organic impurities and volatile components in the adsorption fillers, thereby improving the purity and thermal stability of the fillers. The elution treatment is carried out by acid washing, etc. The method removes excess metal oxides and impurities in the filler to form more adsorption holes and channels. The porous structure provides abundant adsorption sites for lithium ions, thereby improving the adsorption capacity of the adsorbent microspheres. In addition, the surface of the adsorbent filler after acid elution contains abundant oxygen-containing groups and unsaturated metal ion sites. Under alkaline conditions, these functional groups and active sites can be ionized to form negatively charged adsorption centers with a strong affinity for lithium ions in the form of cations. After elution of manganese oxide and lithium oxide, holes with specific sizes and shapes are formed in the material. The size of these holes is similar to the particle size of lithium ions, thereby improving the selective adsorption capacity of the adsorbent microspheres for lithium ions.
[0057] 3. The present invention provides an acid-leached lithium sulfate solution for preparing battery-grade lithium carbonate adsorbent microspheres, wherein the modified chitosan is prepared by modifying 12-crown ether-4 on chitosan molecules, and the modified chitosan is combined with acetic acid and ethanol to form a coagulation bath, and the polysulfone is subjected to chloromethyl modification treatment, and then the modified chitosan is combined with polyethylene glycol 4000 and 3-chloropropyltrimethoxysilane to form a mixed solution. After the mixed solution is added dropwise to the coagulation bath in the form of droplet microspheres, the modified polysulfone in the mixed solution is rapidly solidified to form a microsphere structure, and under alkaline conditions, the modified The modified chitosan is precipitated from the solution, the amino groups on the modified chitosan react with the modified polysulfone or the modified adsorbent microspheres to undergo nucleophilic substitution reaction, and a layer of modified chitosan is coated on the outside of the microspheres to prepare adsorbent microspheres; the 12-crown ether-4 modified on the chitosan has selective recognition ability and strong affinity for lithium ions, and cooperates with the adsorbent filler to further improve the selective adsorption performance of the adsorbent microspheres for lithium under alkaline conditions; the soluble impurities such as polyethylene glycol on the microspheres are eluted by water washing and alcohol washing, thereby increasing the specific surface area of the adsorbent microspheres.
[0058] 4. The invention provides an acid-leached lithium sulfate solution for preparing adsorbent microspheres for battery-grade lithium carbonate. Under acidic conditions, the surface charge of the adsorbent microspheres changes, which weakens the interaction between the adsorbent microspheres and lithium ions, and certain chemical bonds (such as silane bonds, coordination bonds, etc.) in the adsorbent microspheres are attacked by hydrogen ions and broken, which destroys the structural stability of the adsorbent microspheres and further promotes the dissociation of lithium ions. In the adsorbent microspheres, the stability of the adsorbent filler and the protection of the silanization layer make it difficult for the structure to be damaged or the performance to be degraded during the cycle. Although the modified chitosan has a certain sensitivity to acidic and alkaline environments, the selective recognition ability of its crown ether structure and the stability of the chitosan itself make up for this deficiency to a certain extent. In addition, the cross-linked structure of the modified chitosan and the modified polysulfone, with the chemical stability of the modified polysulfone, further improves the overall structural integrity and adsorption performance of the adsorbent microspheres, so that the adsorbent microspheres still have good selectivity and adsorption performance for lithium ions after multiple cycles of regeneration. DETAILED DESCRIPTION
[0059] The technical scheme of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0060] The polysulfone in the present application is selected from Wuhan Kanosi Technology Co., Ltd., and the specification is ordinary bisphenol A type PSF; the polyethylene glycol is polyethylene glycol 4000.
[0061] Example 1
[0062] This embodiment provides a method for preparing battery-grade lithium carbonate adsorbent microspheres by acid leaching lithium sulfate solution, comprising the following steps:
[0063] S1. Preparation of multi-metal mixture
[0064] Manganese carbonate and lithium carbonate were added into a ball mill in a weight ratio of 1:2, ball-milled for 40 min, and passed through a 100-mesh sieve to obtain a mixed powder;
[0065] Weigh: 30 g of mixed powder, 10 g of tetrabutyl titanate, 20 g of ethyl orthosilicate, 200 mL of anhydrous ethanol and 20 g of purified water, add into a reactor and stir, raise the temperature of the reactor to 50°C, keep stirring for 3 hours, raise the temperature of the reactor to 70°C, evaporate the solvent under reduced pressure to obtain a solid, place the solid in a drying oven at 80°C, blow dry for 6 hours, crush, and pass through an 80-mesh sieve to obtain a multi-metal mixture.
[0066] S2, modified adsorption filler
[0067] The multi-metal mixture is placed in a tube furnace, the temperature of the tube furnace is increased to 800°C at a heating rate of 3°C / min, the mixture is kept at this temperature for 4 hours, and the mixture is cooled and discharged to obtain a filler precursor;
[0068] After the filler precursor was continuously eluted with 0.5 mol / L hydrochloric acid for 40 min, it was eluted with purified water for 10 min, and the eluted particles were transferred to a drying oven at a temperature of 75°C and dried to constant weight to obtain an adsorption filler;
[0069] Weigh: 50 g of adsorption filler, 20 g of 3-chloropropyltrimethoxysilane and 300 mL of anhydrous ethanol, add into the reactor and stir, raise the temperature of the reactor to 50°C, add 80 mL of 0.5 mol / L sodium hydroxide solution into the reactor, keep warm and stir for 30 min, lower the temperature of the reactor to room temperature, filter, wash the filter cake with purified water 3 times and then drain, transfer the filter cake to a drying oven at a temperature of 75°C, dry to constant weight, and obtain a modified adsorption filler.
[0070] S3. Preparation of mixed solution
[0071] Weigh: 100 g of polysulfone and 3000 mL of dichloromethane are added to a nitrogen-protected reactor, stirred at room temperature until the polysulfone is dissolved, the reactor temperature is lowered to 6°C, 90 g of trioxymethylene is added to the reactor, stirred for 20 min, 300 mL of trimethylsilyl chloride is added dropwise to the reactor, and then 5 g of anhydrous tin tetrachloride is added to the reactor, and the mixture is stirred and insulated for 25 min. The reactor temperature is raised to reflux, and the reaction is insulated for 12 h. The reactor temperature is lowered to room temperature, 9000 mL of ethanol is slowly added to the reactor, and the mixture is stirred and dispersed for 20 min. The filter cake is washed twice with anhydrous ethanol and then dried. The filter cake is transferred to a drying oven at 50°C and vacuum dried to constant weight to obtain modified polysulfone;
[0072] Weigh: 80 g of modified polysulfone, 100 g of polyethylene glycol 4000 and 600 mL of N,N-dimethylformamide, add into a reactor, raise the temperature of the reactor to 65°C, stir until the system is dissolved, add 200 g of modified adsorption filler into the reactor, stir for 20 min, and vacuum degas to obtain a mixed solution.
[0073] S4. Preparation of coagulation bath
[0074] Chitosan and 2 wt % acetic acid solution were mixed uniformly at a dosage ratio of 1 g:10 mL to obtain a chitosan solution;
[0075] Weigh: 2-hydroxymethyl-12-crown-4 200g, sodium hydride 10g and N,N-dimethylformamide 1000mL, add to a nitrogen-protected reactor and stir, raise the reactor temperature to 55°C, keep warm and stir until the system turns light brown, add epichlorohydrin 90g to the reactor, stir for 70h, add chitosan solution 3000mL to the reactor, keep warm and react for 20h, raise the reactor temperature to 85°C, evaporate the solvent under reduced pressure to obtain a solid, wash the solid with purified water 3 times and then drain, transfer the filter cake to a drying oven at 70°C, and vacuum dry to constant weight to obtain modified chitosan;
[0076] 2 wt % acetic acid solution and ethanol were mixed uniformly in a volume ratio of 4:6 to obtain a dissolving solution;
[0077] The modified chitosan and the dissolving solution were added into the reactor at a ratio of 1 g:7 mL and stirred until the system was dissolved to obtain a coagulation bath.
[0078] S5. Preparation of adsorbent microspheres
[0079] 2 mol / L sodium hydroxide solution and sodium dodecyl sulfate were mixed uniformly in a weight ratio of 10:1 to obtain a sodium hydroxide solution;
[0080] The mixed solution was added dropwise into a reactor equipped with a coagulation bath, aged at room temperature for 40 minutes, the reactor was stirred, sodium hydroxide solution was added dropwise into the reactor, the pH of the system was adjusted to 9, stirred for 3 hours, filtered, the filter cake was washed with purified water until neutral and then dried, the filter cake was transferred to a drying oven at a temperature of 70°C, and vacuum dried to constant weight to obtain a crude adsorbent, wherein the volume ratio of the mixed solution to the coagulation bath was 1:3;
[0081] The crude adsorbent and anhydrous ethanol were added into the reactor in a ratio of 1g:20mL and stirred. The temperature of the reactor was raised to 60°C and stirred for 40min. The temperature of the reactor was lowered to room temperature and filtered. The filter cake was washed with purified water three times and then dried. The filter cake was transferred to a drying oven at 70°C and vacuum dried to constant weight to obtain adsorbent microspheres.
[0082] Example 2
[0083] This embodiment provides a method for preparing battery-grade lithium carbonate adsorbent microspheres by acid leaching lithium sulfate solution, comprising the following steps:
[0084] S1. Preparation of multi-metal mixture
[0085] Manganese carbonate and lithium carbonate were added into a ball mill in a weight ratio of 1:2, ball-milled for 50 min, and passed through a 100-mesh sieve to obtain a mixed powder;
[0086] Weigh: 30 g of mixed powder, 10 g of tetrabutyl titanate, 20 g of ethyl orthosilicate, 200 mL of anhydrous ethanol and 20 g of purified water, add into a reactor and stir, raise the temperature of the reactor to 55°C, keep stirring for 4 hours, raise the temperature of the reactor to 75°C, evaporate the solvent under reduced pressure to obtain a solid, place the solid in a drying oven at 85°C, blow dry for 7 hours, crush, and pass through an 80-mesh sieve to obtain a multi-metal mixture.
[0087] S2, modified adsorption filler
[0088] The multi-metal mixture is placed in a tube furnace, the temperature of the tube furnace is increased to 850°C at a heating rate of 4°C / min, and the mixture is kept at this temperature for 5 hours, and then the mixture is cooled and discharged to obtain a filler precursor;
[0089] After the filler precursor was continuously eluted with 0.5 mol / L hydrochloric acid for 50 min, it was eluted with purified water for 13 min, and the eluted particles were transferred to a drying oven at 80°C and dried to constant weight to obtain an adsorption filler;
[0090] Weigh: 50 g of adsorption filler, 20 g of 3-chloropropyltrimethoxysilane and 300 mL of anhydrous ethanol, add into the reactor and stir, raise the temperature of the reactor to 55°C, add 80 mL of 0.5 mol / L sodium hydroxide solution into the reactor, keep warm and stir for 40 min, lower the temperature of the reactor to room temperature, filter, wash the filter cake with purified water 3 times and then drain, transfer the filter cake into a drying oven at 80°C, dry to constant weight, and obtain a modified adsorption filler.
[0091] S3. Preparation of mixed solution
[0092] Weigh: 100 g of polysulfone and 3000 mL of dichloromethane are added to a nitrogen-protected reactor, stirred at room temperature until the polysulfone is dissolved, the reactor temperature is lowered to 7°C, 90 g of trioxymethylene is added to the reactor, stirred for 25 min, 300 mL of trimethylsilyl chloride is added dropwise to the reactor, and then 5 g of anhydrous tin tetrachloride is added to the reactor, stirred for 30 min, the reactor temperature is raised to reflux, the reaction is kept warm for 14 h, the reactor temperature is lowered to room temperature, 9000 mL of ethanol is slowly added to the reactor, stirred and dispersed for 25 min, filtered, the filter cake is washed twice with anhydrous ethanol and then dried, the filter cake is transferred to a drying oven at a temperature of 55°C, and vacuum dried to constant weight to obtain modified polysulfone;
[0093] Weigh: 90 g of modified polysulfone, 110 g of polyethylene glycol 4000 and 600 mL of N,N-dimethylformamide and add them into a reactor. Raise the temperature of the reactor to 70°C and stir until the system is dissolved. Add 225 g of modified adsorption filler into the reactor, stir for 25 min, and perform vacuum degassing to obtain a mixed solution.
[0094] S4. Preparation of coagulation bath
[0095] Chitosan and 2 wt % acetic acid solution were mixed uniformly at a dosage ratio of 1 g:10 mL to obtain a chitosan solution;
[0096] Weigh: 2-hydroxymethyl-12-crown-4 200g, sodium hydride 10g and N,N-dimethylformamide 1000mL, add to a nitrogen-protected reactor and stir, raise the reactor temperature to 60°C, keep warm and stir until the system turns light brown, add epichlorohydrin 90g to the reactor, stir for 75h, add chitosan solution 3000mL to the reactor, keep warm and react for 25h, raise the reactor temperature to 90°C, evaporate the solvent under reduced pressure to obtain a solid, wash the solid with purified water 3 times and then drain, transfer the filter cake to a drying oven at a temperature of 75°C, and vacuum dry to constant weight to obtain modified chitosan;
[0097] 2 wt % acetic acid solution and ethanol were mixed uniformly in a volume ratio of 4:6 to obtain a dissolving solution;
[0098] The modified chitosan and the dissolving solution were added into the reactor at a ratio of 1 g:7 mL and stirred until the system was dissolved to obtain a coagulation bath.
[0099] S5. Preparation of adsorbent microspheres
[0100] 2 mol / L sodium hydroxide solution and sodium dodecyl sulfate were mixed uniformly in a weight ratio of 10:1 to obtain a sodium hydroxide solution;
[0101] The mixed solution was added dropwise into a reactor equipped with a coagulation bath, aged at room temperature for 50 min, the reactor was stirred, sodium hydroxide solution was added dropwise into the reactor, the pH of the system was adjusted to 9.5, stirred for 4 h, filtered, the filter cake was washed with purified water until neutral and then dried, the filter cake was transferred to a drying oven at a temperature of 75°C, and vacuum dried to constant weight to obtain a crude adsorbent, wherein the volume ratio of the mixed solution to the coagulation bath was 1:3;
[0102] The crude adsorbent and anhydrous ethanol were added into the reactor in a ratio of 1 g:20 mL and stirred. The temperature of the reactor was raised to 65°C and stirred for 50 min. The temperature of the reactor was lowered to room temperature and filtered. The filter cake was washed three times with purified water and then dried. The filter cake was transferred to a drying oven at 75°C and vacuum dried to constant weight to obtain adsorbent microspheres.
[0103] Example 3
[0104] This embodiment provides a method for preparing battery-grade lithium carbonate adsorbent microspheres by acid leaching lithium sulfate solution, comprising the following steps:
[0105] S1. Preparation of multi-metal mixture
[0106] Manganese carbonate and lithium carbonate were added into a ball mill in a weight ratio of 1:2, ball-milled for 60 min, and passed through a 100-mesh sieve to obtain a mixed powder;
[0107] Weigh: 30 g of mixed powder, 10 g of tetrabutyl titanate, 20 g of ethyl orthosilicate, 200 mL of anhydrous ethanol and 20 g of purified water, add into a reactor and stir, raise the temperature of the reactor to 60°C, keep stirring for 5 hours, raise the temperature of the reactor to 80°C, evaporate the solvent under reduced pressure to obtain a solid, place the solid in a drying oven at 90°C, blow dry for 8 hours, crush, and pass through an 80-mesh sieve to obtain a multi-metal mixture.
[0108] S2, modified adsorption filler
[0109] The multi-metal mixture is placed in a tube furnace, the temperature of the tube furnace is increased to 900°C at a heating rate of 5°C / min, the mixture is kept at this temperature for 6 hours, and the mixture is cooled and discharged to obtain a filler precursor;
[0110] After the filler precursor was continuously eluted with 0.5 mol / L hydrochloric acid for 60 min, it was eluted with purified water for 15 min, and the eluted particles were transferred to a drying oven at 85°C and dried to constant weight to obtain an adsorption filler;
[0111] Weigh: 50 g of adsorption filler, 20 g of 3-chloropropyltrimethoxysilane and 300 mL of anhydrous ethanol, add into the reactor and stir, raise the temperature of the reactor to 60°C, add 80 mL of 0.5 mol / L sodium hydroxide solution into the reactor, keep warm and stir for 50 min, lower the temperature of the reactor to room temperature, filter, wash the filter cake with purified water 3 times and then drain, transfer the filter cake into a drying oven at 85°C, dry to constant weight, and obtain a modified adsorption filler.
[0112] S3. Preparation of mixed solution
[0113] Weigh: 100 g of polysulfone and 3000 mL of dichloromethane are added to a nitrogen-protected reactor, stirred at room temperature until the polysulfone is dissolved, the reactor temperature is lowered to 8°C, 90 g of trioxymethylene is added to the reactor, stirred for 30 min, 300 mL of trimethylsilyl chloride is added dropwise to the reactor, and then 5 g of anhydrous tin tetrachloride is added to the reactor, stirred for 35 min, the reactor temperature is raised to reflux, the reaction is kept warm for 16 h, the reactor temperature is lowered to room temperature, 9000 mL of ethanol is slowly added to the reactor, stirred and dispersed for 30 min, filtered, the filter cake is washed twice with anhydrous ethanol and then dried, the filter cake is transferred to a drying oven at a temperature of 60°C, and vacuum dried to constant weight to obtain modified polysulfone;
[0114] Weigh: 100 g of modified polysulfone, 120 g of polyethylene glycol 4000 and 600 mL of N,N-dimethylformamide, add into a reactor, raise the temperature of the reactor to 75°C, stir until the system is dissolved, add 250 g of modified adsorption filler into the reactor, stir for 30 min, and vacuum degas to obtain a mixed solution.
[0115] S4. Preparation of coagulation bath
[0116] Chitosan and 2 wt % acetic acid solution were mixed uniformly at a dosage ratio of 1 g:10 mL to obtain a chitosan solution;
[0117] Weigh: 2-hydroxymethyl-12-crown-4 200g, sodium hydride 10g and N,N-dimethylformamide 1000mL, add to a nitrogen-protected reactor and stir, raise the reactor temperature to 65°C, keep warm and stir until the system turns light brown, add epichlorohydrin 90g to the reactor, stir for 80h, add chitosan solution 3000mL to the reactor, keep warm and react for 30h, raise the reactor temperature to 95°C, evaporate the solvent under reduced pressure to obtain a solid, wash the solid with purified water 3 times and then drain, transfer the filter cake to a drying oven at 80°C, and vacuum dry to constant weight to obtain modified chitosan;
[0118] 2 wt % acetic acid solution and ethanol were mixed uniformly in a volume ratio of 4:6 to obtain a dissolving solution;
[0119] The modified chitosan and the dissolving solution were added into the reactor at a ratio of 1 g:7 mL and stirred until the system was dissolved to obtain a coagulation bath.
[0120] S5. Preparation of adsorbent microspheres
[0121] 2 mol / L sodium hydroxide solution and sodium dodecyl sulfate were mixed uniformly in a weight ratio of 10:1 to obtain a sodium hydroxide solution;
[0122] The mixed solution was added dropwise into a reactor equipped with a coagulation bath, aged at room temperature for 60 minutes, the reactor was stirred, sodium hydroxide solution was added dropwise into the reactor, the pH of the system was adjusted to 10, stirred for 5 hours, filtered, the filter cake was washed with purified water until neutral, and then dried, the filter cake was transferred to a drying oven at a temperature of 80°C, and vacuum dried to constant weight to obtain a crude adsorbent, wherein the volume ratio of the mixed solution to the coagulation bath was 1:3;
[0123] The crude adsorbent and anhydrous ethanol were added into the reactor in a ratio of 1 g:20 mL and stirred. The temperature of the reactor was raised to 70°C and stirred for 60 min. The temperature of the reactor was lowered to room temperature and filtered. The filter cake was washed three times with purified water and then dried. The filter cake was transferred to a drying oven at 80°C and vacuum dried to constant weight to obtain adsorbent microspheres.
[0124] Example 4
[0125] This embodiment provides a method for preparing battery-grade lithium carbonate by acid leaching lithium sulfate solution, comprising the following steps:
[0126] Step 1, adding the acid leaching extract to the reactor and stirring, lowering the temperature of the reactor to 15°C, adding calcium hydroxide solution to the reactor, adjusting the system pH to 9, raising the temperature of the reactor to room temperature, stirring for 20 minutes, filtering, washing the filter cake twice with 3wt% sodium hydroxide solution and then draining, collecting the filtrate to obtain a pretreatment solution;
[0127] Step 2: Add the pretreatment solution and the adsorbent microspheres prepared in Example 1 into the reactor at a ratio of 50 mL:2 g, stir at room temperature for 50 min, filter, wash the filter cake twice with a sodium hydroxide solution at pH = 9 and then drain to obtain adsorption saturated adsorbent microspheres;
[0128] Step 3: Add the adsorbent microspheres saturated with adsorption and 0.5 mol / L hydrochloric acid solution into the reactor at a dosage ratio of 1 g: 5 mL and stir, raise the temperature of the reactor to 40° C., keep warm for 30 min, filter, wash the filter cake twice with 0.5 mol / L hydrochloric acid solution and then drain, collect the filtrate to obtain a lithium-containing purified liquid;
[0129] Step 4: add saturated sodium carbonate solution to the lithium-containing purified liquid, adjust the system pH to 8, stir for 20 minutes, filter, wash the filter cake with 3°C purified water three times and then drain, transfer the filter cake to a drying oven at a temperature of 70°C, and vacuum dry to constant weight to obtain crude lithium carbonate;
[0130] Step 5. Add crude lithium carbonate and deionized water in a ratio of 1g:10mL to a reactor, raise the temperature of the reactor to 85°C, stir until the system is dissolved, filter while hot into a crystallization kettle and stir, lower the temperature of the crystallization kettle to 15°C, a large amount of solid precipitates, filter, wash the filter cake three times with 50vol% anhydrous ethanol aqueous solution and then drain, dry the filter cake at 70°C, transfer to a tubular furnace at 250°C, and dry to constant weight to obtain lithium carbonate.
[0131] Example 5
[0132] This embodiment provides a method for preparing battery-grade lithium carbonate by acid leaching lithium sulfate solution, comprising the following steps:
[0133] Step 1, adding the acid leaching extract to the reactor and stirring, lowering the temperature of the reactor to 20°C, adding calcium hydroxide solution to the reactor, adjusting the system pH to 9.5, raising the temperature of the reactor to room temperature, stirring for 25 minutes, filtering, washing the filter cake twice with 3wt% sodium hydroxide solution and then draining, collecting the filtrate to obtain a pretreatment solution;
[0134] Step 2: Add the pretreatment solution and the adsorbent microspheres prepared in Example 2 into the reactor in a ratio of 50 mL:2.5 g, stir at room temperature for 55 min, filter, wash the filter cake twice with a sodium hydroxide solution with a pH of 9.5, and then drain to obtain adsorption-saturated adsorbent microspheres;
[0135] Step 3: Add the adsorbent microspheres saturated with adsorption and 0.5 mol / L hydrochloric acid solution into the reactor at a dosage ratio of 1 g: 5 mL and stir, raise the temperature of the reactor to 45° C., keep warm for 40 min, filter, wash the filter cake twice with 0.5 mol / L hydrochloric acid solution and then drain, collect the filtrate to obtain a purified lithium-containing liquid;
[0136] Step 4: Add saturated sodium carbonate solution to the lithium-containing purified liquid, adjust the system pH to 8.5, stir for 25 minutes, filter, wash the filter cake with 5°C purified water three times and then drain, transfer the filter cake to a drying oven at a temperature of 75°C, and vacuum dry to constant weight to obtain crude lithium carbonate;
[0137] Step 5. Add crude lithium carbonate and deionized water in a ratio of 1g:10mL to a reactor, raise the temperature of the reactor to 90°C, stir until the system is dissolved, filter while hot into a crystallization kettle and stir, lower the temperature of the crystallization kettle to 17°C, a large amount of solid precipitates, filter, wash the filter cake with 50vol% anhydrous ethanol aqueous solution 3 times and then drain, dry the filter cake at 75°C, transfer to a tubular furnace at 255°C, and dry to constant weight to obtain lithium carbonate.
[0138] Example 6
[0139] This embodiment provides a method for preparing battery-grade lithium carbonate by acid leaching lithium sulfate solution, comprising the following steps:
[0140] Step 1, adding the acid leaching extract to the reactor and stirring, lowering the temperature of the reactor to 25°C, adding calcium hydroxide solution to the reactor, adjusting the system pH to 10, raising the temperature of the reactor to room temperature, stirring for 30 minutes, filtering, washing the filter cake twice with 3wt% sodium hydroxide solution and then draining, collecting the filtrate to obtain a pretreatment solution;
[0141] Step 2: Add the pretreatment solution and the adsorbent microspheres prepared in Example 3 into the reactor at a ratio of 50 mL:3 g, stir at room temperature for 60 min, filter, wash the filter cake twice with a sodium hydroxide solution with a pH of 10, and then drain to obtain adsorption-saturated adsorbent microspheres;
[0142] Step 3: Add the adsorbent microspheres saturated with adsorption and 0.5 mol / L hydrochloric acid solution into the reactor at a dosage ratio of 1 g: 5 mL and stir, raise the temperature of the reactor to 50° C., keep warm for 50 min, filter, wash the filter cake twice with 0.5 mol / L hydrochloric acid solution and then drain, collect the filtrate to obtain a purified lithium-containing liquid;
[0143] Step 4: Add saturated sodium carbonate solution to the lithium-containing purified liquid, adjust the system pH to 9, stir for 30 minutes, filter, wash the filter cake with 8°C purified water three times and then drain, transfer the filter cake to a drying oven at a temperature of 80°C, and vacuum dry to constant weight to obtain crude lithium carbonate;
[0144] Step 5. Add crude lithium carbonate and deionized water in a ratio of 1g:10mL to a reactor, raise the temperature of the reactor to 95°C, stir until the system is dissolved, filter while hot into a crystallization kettle and stir, lower the temperature of the crystallization kettle to 18°C, a large amount of solid precipitates, filter, wash the filter cake three times with 50vol% anhydrous ethanol aqueous solution and then drain, dry the filter cake at 80°C, transfer to a tubular furnace at 260°C, and dry to constant weight to obtain lithium carbonate.
[0145] Comparative Example 1
[0146] The difference between this comparative example and Example 6 is that in the preparation process of the adsorbent microspheres used, no manganese carbonate is added in step S1.
[0147] Comparative Example 2
[0148] The difference between this comparative example and Example 6 is that in the preparation process of the adsorbent microspheres used, the adsorbent filler in step S2 replaces the modified adsorbent filler in step S3.
[0149] Comparative Example 3
[0150] The difference between this comparative example and Example 6 is that in the preparation process of the adsorbent microspheres used, the coagulation bath in step S4 is replaced by chitosan instead of modified chitosan.
[0151] Comparative Example 4
[0152] The difference between this comparative example and Example 6 is that in step 1, the calcium hydroxide solution is replaced by sodium hydroxide solution.
[0153] Performance Test:
[0154] The chemical composition of the lithium carbonate materials prepared in Examples 4-6 and Comparative Examples 1-4 was tested and analyzed with reference to the standard YS / T 582-2023 "Battery Grade Lithium Carbonate";
[0155] According to the formula The recovery rate of lithium in Examples 4-6 and Comparative Examples 1-4 was measured, where: is the mass of lithium carbonate obtained in step 5, is the content of lithium carbonate in the lithium carbonate obtained in step 5, V 预处理溶液 is the volume of the pretreatment solution obtained in step 1, W 预处理溶液-Li is the lithium content in the pretreatment solution obtained in step 1;
[0156] The adsorbent microspheres were recycled, and the purity of lithium carbonate and the recovery rate of lithium were tested after the adsorbent microspheres were recycled 20 times. The specific test results are shown in Table 1-2.
[0157] Table 1 - Performance test data of adsorbent microspheres for the first time use
[0158]
[0159]
[0160] Table 2 - Performance test data of adsorbent microspheres after 20th use in cycle
[0161]
[0162]
[0163] Data Analysis:
[0164] Comparative analysis of the data in Table 1 above shows that the content of lithium carbonate prepared by the present invention reaches 99.76%, and all impurities meet the requirements of Li2CO3-D2 in battery-grade lithium carbonate, and the recovery rate of lithium in waste liquid reaches 88.4%. After 20 cycles of use, the content of lithium carbonate reaches 99.62%, and all impurities meet the requirements of Li2CO3-D2 in battery-grade lithium carbonate, and the recovery rate of lithium in waste liquid reaches 86.8%. In the comparative example, for products with a lithium carbonate content of less than 99.5%, the contents of various impurities therein are not further tested. Compared with the comparative example, the performance parameters of the embodiment are better than those of the comparative example;
[0165] It is explained that the present invention is to prepare an adsorption filler by using a mixed powder composed of manganese carbonate and lithium carbonate, tetrabutyl titanate and tetraethyl orthosilicate as raw materials, and then solidify and form it with chloromethyl-modified polysulfone and polyethylene glycol in a coagulation bath of 12-crown ether-4 modified chitosan to obtain renewable and recyclable adsorbent microspheres, and then optimize the regeneration and recovery process of the acid leaching extract, not only can the lithium in the acid leaching extract be selectively adsorbed and recovered, thereby improving the purity of the lithium carbonate, but also reducing the traditional distillation and concentration steps, simplifying the regeneration process of the lithium carbonate, and reducing the production cost.
[0166] The above contents are merely examples and explanations of the structure of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the structure of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.
[0167] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0168] The preferred embodiments of the present invention disclosed above are only used to help explain the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to only specific implementation methods. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.
Claims
1. A method for preparing battery-grade lithium carbonate by acid leaching lithium sulfate solution, characterized in that: The following steps are involved: S1. Add the acid leaching extract to the reactor and stir. Lower the temperature of the reactor to 15-25°C, add calcium hydroxide solution to the reactor, adjust the pH of the system to 9-10, raise the temperature of the reactor to room temperature, stir for 20-30 minutes, and post-treat to obtain a pre-treated solution; S2, adding the pretreatment solution and the adsorbent microspheres into a reaction kettle and stirring, stirring for 50-60 minutes at room temperature, and post-treating to obtain adsorption-saturated adsorbent microspheres; S3, desorbing the adsorbent microspheres to obtain a lithium-containing purified liquid; S4, adding saturated sodium carbonate solution to the lithium-containing purified liquid, adjusting the system pH to 8-9, and post-treating to obtain crude lithium carbonate; S5. Purify the crude lithium carbonate to obtain lithium carbonate.
2. The method for preparing battery-grade lithium carbonate by acid leaching lithium sulfate solution according to claim 1, characterized in that: In step S2, the ratio of the pretreatment solution to the adsorbent microspheres is 50 mL: 2-3 g.
3. The method for preparing battery-grade lithium carbonate by acid leaching lithium sulfate solution according to claim 1, characterized in that: The adsorbent microspheres are processed by the following steps: A1, polysulfone and dichloromethane are added to a nitrogen-protected reactor, stirred at room temperature until the polysulfone is dissolved, the reactor temperature is lowered to 6-8°C, trioxymethylene is added to the reactor, stirred for 20-30 minutes, trimethylsilyl chloride is added dropwise to the reactor, and then a catalyst is added to the reactor, stirred for 25-35 minutes, the reactor temperature is raised to reflux, the reaction is kept warm for 12-16 hours, and post-processed to obtain modified polysulfone; A2, adding modified polysulfone, polyethylene glycol and N,N-dimethylformamide into a reactor, raising the temperature of the reactor to 65-75°C, stirring until the system is dissolved, adding modified adsorption filler into the reactor, stirring for 20-30 minutes, vacuum degassing, and obtaining a mixed solution; A3, the mixed solution was added dropwise into a reactor equipped with a coagulation bath, aged at room temperature for 40-60 min, the reactor was stirred, sodium hydroxide solution was added dropwise into the reactor, the pH of the system was adjusted to 9-10, stirred for 3-5 h, and post-processed to obtain a crude adsorbent; A4. Add the crude adsorbent and anhydrous ethanol into a reactor and stir. Raise the temperature of the reactor to 60-70°C and stir for 40-60 minutes. Post-treat to obtain adsorbent microspheres.
4. The method for preparing battery-grade lithium carbonate by acid leaching lithium sulfate solution according to claim 3, characterized in that: In step A1, the amount ratio of the polysulfone, dichloromethane, trioxymethylene, trimethylsilyl chloride and the catalyst is 10g:300mL:9g:30mL:0.5g, and the catalyst is anhydrous tin tetrachloride; in step A2, the amount ratio of the modified polysulfone, polyethylene glycol, N,N-dimethylformamide and the modified adsorption filler is 8-10g:10-12g:60mL:20-25g; in step A3, the volume ratio of the mixed solution to the coagulation bath is 1:3, and the sodium hydroxide solution is composed of 2mol / L sodium hydroxide solution and sodium dodecyl sulfate in a weight ratio of 10:1; in step A4, the amount ratio of the crude adsorbent to anhydrous ethanol is 1g:20mL.
5. The method for preparing battery-grade lithium carbonate by acid leaching lithium sulfate solution according to claim 3, characterized in that: The modified adsorption filler in step A is obtained by processing the following steps: B1. Place the multi-metal mixture in a tube furnace, increase the temperature of the tube furnace to 800-900°C at a heating rate of 3-5°C / min, keep the mixture warm for 4-6 hours, cool it down and discharge it to obtain a filler precursor; B2. After continuously eluting the filler precursor with 0.5 mol / L hydrochloric acid for 40-60 min, use purified water to elute for 10-15 min, transfer the eluted particles to a drying oven at a temperature of 75-85°C, and dry to constant weight to obtain an adsorption filler; B3. Add the adsorption filler, 3-chloropropyltrimethoxysilane and anhydrous ethanol into the reactor and stir. The temperature of the reactor is raised to 50-60° C., and alkali solution is added into the reactor. The reaction mixture is stirred for 30-50 min at the temperature. The modified adsorption filler is obtained by post-treatment.
6. The method for preparing battery-grade lithium carbonate by acid leaching lithium sulfate solution according to claim 5, characterized in that: In step B3, the usage ratio of the adsorption filler, 3-chloropropyltrimethoxysilane, anhydrous ethanol and alkali solution is 5g:2g:30mL:8mL, and the alkali solution is 0.5mol / L sodium hydroxide solution.
7. The method for preparing battery-grade lithium carbonate by acid leaching lithium sulfate solution according to claim 5, characterized in that: The multi-metal mixture is obtained by the following steps: C1. Add manganese carbonate and lithium carbonate into a ball mill, ball mill for 40-60 minutes, and pass through a 100-mesh sieve to obtain a mixed powder; C2. Add the mixed powder, tetrabutyl titanate, ethyl orthosilicate, anhydrous ethanol and purified water into a reactor and stir. The temperature of the reactor is raised to 50-60° C. and stirred for 3-5 hours. Post-process to obtain a multi-metal mixture.
8. The method for preparing battery-grade lithium carbonate by acid leaching lithium sulfate solution according to claim 7, characterized in that: In step C1, the weight ratio of manganese carbonate to lithium carbonate is 1:2; in step C2, the usage ratio of the mixed powder, tetrabutyl titanate, ethyl orthosilicate, anhydrous ethanol and purified water is 3g:1g:2g:20mL:2g.
9. The method for preparing battery-grade lithium carbonate by acid leaching lithium sulfate solution according to claim 3, characterized in that: The coagulation bath is processed by the following steps: D1. Add 2-hydroxymethyl-12-crown-4, sodium hydride and N,N-dimethylformamide to a nitrogen-protected reactor and stir. Raise the temperature of the reactor to 55-65°C, keep warm and stir until the system turns light brown. Add epichlorohydrin to the reactor and stir for 70-80h. Add chitosan solution to the reactor and keep warm for 20-30h. Post-treat to obtain modified chitosan. D2. Add the modified chitosan and the dissolving solution into the reactor and stir until the system is dissolved to obtain a coagulation bath.
10. The method for preparing battery-grade lithium carbonate by acid leaching lithium sulfate solution according to claim 9, characterized in that: In step D1, the amount ratio of 2-hydroxymethyl-12-crown-4, sodium hydride, N,N-dimethylformamide, epichlorohydrin and chitosan solution is 2g:0.1g:10mL:0.9g:30mL, and the chitosan solution is composed of chitosan and 2wt% acetic acid solution in a ratio of 1g:10mL; in step D2, the amount ratio of the modified chitosan and the dissolving solution is 1g:7mL, and the dissolving solution is composed of 2wt% acetic acid solution and ethanol in a volume ratio of 4:6.
